Electrochemical magnetic beads-based immunosensing platform for the determination of α-lactalbumin in milk. (15th December 2016) - Ruiz-Valdepeñas Montiel, Víctor; Campuzano, Susana; Torrente-Rodríguez, Rebeca M.; Reviejo, A. Julio; Pingarrón, José M.
Graphical abstract: Highlights: First amperometric MBs-based immunosensor for α-LA with excellent sensitivity (LOD 11.0 pg mL −1 ) and selectivity. Determination of α-LA in different milk samples and infant formulas. Good correlation against results provided by a commercial ELISA spectrophotometric kit. Powerful analytical tool for food safety and consumer protection. Abstract: Alpha-lactalbumin (α-LA) is one of the whey proteins in cows' milk that has been identified as allergenic. In this work, we present, for the first time, a very sensitive magnetic beads (MBs)-based immunosensor for the determination of α-LA. A sandwich configuration involving selective capture and horseradish peroxidase-labeled detector antibodies was implemented on carboxylic acid-modified magnetic beads, captured magnetically under the surface of a disposable screen-printed carbon electrode for amperometric detection using the hydroquinone (HQ)/H2 O2 system. The α-LA immunosensor exhibited a wide linear range (37.0–5000 pg/ml), a low limit of detection (LOD, 11.0 pg/ml) and noteworthy selectivity against other non-target proteins. The MBs-based immunosensing platform was applied successfully for the determination of α-LA in several varieties of milk (raw and UHT cows' milk as well as human milk) and infant formulations. The results were corroborated with those obtained using a commercial ELISA method, thereby substantiating the analytical merits of this unique method.